The History of the Becoming of the Self-Conscious Soul as the Culminating - T. A. Koshemchuk (Концепт: философия, религия, культура, 2021)
The article dwells on the amalgam of meanings and interpretations that have arisen in connection to Andrei Bely’s major work of the 1920s The History of the Becoming of the Self-Conscious Soul. This paper is dedicated to the first complete edition of this literature and philosophical piece that took place in 2020, two decades after the book was first — and partially — published in 1999. The very process of publishing and the temporal gaps that marked the stages in the life of this work is important for better understanding of the trends in interpreting the motifs and concepts of Bely. This study anticipates the inconsistencies of various attempts to understand the conceptual mechanism of Bely and thus has the scope of clarifying such concerning takes and contrasting them to the ways of addressing conceptual issues that Bely uses in his entire oeuvre. With the 1999 publication fueling interest to the self-conscious soul, it represented, however, just a first approximation — and this one, quite incoherent in interpretations, should be amplified towards a fuller elaboration. The analyzed corpus of secondary literature reveals that in a few articles devoted to main ideas of The History of the Becoming of the Self-Conscious Soul there are numerous inaccuracies of perception and reinterpretation even in the basic concepts. For better understanding of Bely, it is fruitful to consider his ideas not from outside worldview positions. Quite the opposite, do it with the view to internal consonance, to anthroposophical foundations. Otherwise, misunderstanding of such concepts as culture, individual, I, personality, self-consciousness is inevitable. The article notes a number of features of their modern perception. First, these concepts are taken not in the dynamic, variable, gradational way, but in a rational and static way, with one or more meaning torn out of the variation series. Further, Bely, contrary to his own judgments about the Steinerian foundations of his work, is considered to have various influences and parallels, based on external similarities. Finally, Bely’s anthroposophical ideas themselves are reinterpreted and radical differences in comparison with anthroposophy are found. The article also reveals fruitful judgments about the essence of The Нistory and examines first of all the articles of Karen A. Swassjan who examines Bely’s history of culture as a personal history of the formation of consciousness — as material for a biography.